Non‐Equilibrium Dielectric Barrier Discharge Treatment of Mesenchymal Stem Cells: Charges and Reactive Oxygen Species Play the Major Role in Cell Death. Issue 10 (14th April 2015) - Lin, Abraham; Chernets, Natalie; Han, Justine; Alicea, Yordano; Dobrynin, Danil; Fridman, Gregory; Freeman, Theresa A.; Fridman, Alexander; Miller, Vandana
Abstract : Atmospheric pressure non‐equilibrium plasmas are efficacious in killing both prokaryotic and eukaryotic cells. While the mechanism of plasma induced cell death has been thoroughly studied in prokaryotes, detailed investigation of plasma mediated eukaryotic cell death is still pending. When plasma is generated, four major components that interact with cells are produced: electric fields, radiation, charged particles, and neutral gas species. The goal of this study was to determine which of the plasma components are responsible for plasma‐induced cell death by isolating and removing each from treatment. The C3H10T1/2 murine mesenchyme stem cell line was treated in six well plates, stained with Propidium Iodide to determine viability, and analyzed by image cytometry. Our results show that plasma‐generated charges and reactive oxygen species are the primary contributors to cell death. Abstract : We determined the components of non‐thermal, atmospheric plasma that contribute to murine mesenchymal stem cell death. When plasma is generated for biological treatments, four major components are produced: electric fields, radiation, charged particles, and neutral gas species. We isolated and removed each from nanosecond pulsed dielectric barrier discharge (nspDBD) plasma treatment and evaluated cell viability. We determined that plasma generated charges and reactive oxygen species play the major role in cell death in this system.